Harnojoyo's Technocratic Populism in Building the City of Palembang - Primananda Gumay, Pratama; Izomiddin, Izomiddin; Harahap, Raegen; Gumay, Pratama Primandani (Prodi Ilmu Politik FISIP Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research is entitled Populist Politics Harnojoyo (Analysis of Palembang City Development Strategies). The purpose of this study is to see Harnojoyo's populist forms and how Harnojoyo's populist activities in Palembang City. The research method used is descriptive with a qualitative approach. Data collection techniques with literature study and decommunation. Primary data sources through observations of events regarding Harnojoyo's policies, secondary data sources in the form of books, journals, writings and the results of populist analysis, articles, internet, news. The theory used is populist theory. The results of Harnojoyo's populist political research show that working for the people and power to produce populist programs and at the same time absorb people's aspirations to build Palembang city is seen as still listening to people's aspirations, Harnojoyo's populist is a strategy to win people's hearts.